Magnetoliposomes as Contrast Agents for Longitudinal in vivo Assessment of Transplanted Pancreatic Islets in a Diabetic Rat Model - Garcia Ribeiro, Rita Sofia; Gysemans, Conny; da Cunha, João Paulo Monteiro Carvalho Mori; Manshian, Bella B; Jirak, Daniel; Kriz, Jan; Gallo, Juan; Bañobre-López, Manuel; Struys, Tom; De Cuyper, Marcel; Mathieu, Chantal; Soenen, Stefaan J; et al. (Scientific reports, 2018)
Magnetoliposomes (MLs) were synthesized and tested for longitudinal monitoring of transplanted pancreatic islets using magnetic resonance imaging (MRI) in rat models. The rat insulinoma cell line INS-1E and isolated pancreatic islets from outbred and inbred rats were used to optimize labeling conditions in vitro. Strong MRI contrast was generated by islets exposed to 50 µg Fe/ml for 24 hours without any increased cell death, loss of function or other signs of toxicity. In vivo experiments showed that pancreatic islets (50-1000 units) labeled with MLs were detectable for up to 6 weeks post-transplantation in the kidney subcapsular space. Islets were also monitored for two weeks following transplantation through the portal vein of the liver. Hereby, islets labeled with MLs and transplanted under the left kidney capsule were able to correct hyperglycemia and had stable MRI signals until nephrectomy. Interestingly, in vivo MRI of streptozotocin induced diabetic rats transplanted with allogeneic islets demonstrated loss of MRI contrast between 7-16 days, indicative of loss of islet structure. MLs used in this study were not only beneficial for monitoring the location of transplanted islets in vivo with high sensitivity but also reported on islet integrity and hereby indirectly on islet function and rejection.
Keywords: magnetické nanočástice; Liver; kultivované buňky; longitudinální studie; Rats; játra; Contrast Media; vena portae; Streptozocin; inzulin; Rats, Wistar; Insulin; kontrastní látky; Islets of Langerhans; Hyperglycemia; Langerhansovy ostrůvky; krysa rodu Rattus; hyperglykemie; Portal Vein; magnetická rezonanční tomografie; experimentální diabetes mellitus; Cells, Cultured; Magnetic Resonance Imaging; zvířata; transplantace Langerhansových ostrůvků; Magnetite Nanoparticles; Diabetes Mellitus, Experimental; potkani inbrední LEW; Islets of Langerhans Transplantation; Rats, Inbred Lew; potkani Wistar; Longitudinal Studies; streptozocin; Animals